Analisis Perilaku Pelat dari Baja Hollow dengan Pengisian Mortar FAS 0,4 terhadap Variasi Ukuran dan Tebal Profil Baja Hollow - Huzaim, Huzaim; Putra, Rudiansyah; Humayra, Siti; Dany Dhaifullah, Teuku; Sanitra, Roni (JURNAL TEKNIK SIPIL, 2022)
The development of the times and science, especially in the field of civil engineering requires an increase in the quality of civil engineering structures so that many innovations are found with the use of steel profiles. One type of steel profile that can be found is the hollow steel profile. As a construction element, hollow steel has a weakness in carrying loads, this is because of the strength in the middle profile so that the hollow steel structure becomes more slender and prone to bending. To overcome these weaknesses, it is possible to fill in the mortar in the middle of the profile. The purpose of this study is to analyze the value of the capacity of the plate structure made of hollow steel structure by analyzing 3 types of capacity, namely yield capacity, maximum capacity, and allowable capacity. Broadly speaking, in this study 5 specimens were made which were divided into 2 variations of test objects, namely variations in profile sizes and variations in thickness of hollow steel profiles, each plate specimen being named BU1, BU2, BU3, BU4, and BU5. The results showed that there was a correlation between the size of the profile and the profile of the slab capacity value, where the larger the size and thickness of the profile, the better the capacity of the slab to withstand the load.